Pengaruh Kompetensi Pedagogik dan Profesional Dosen Terhadap Indeks Prestasi Mahasiswa Semester II AKJP II Pekanbaru - Anna Maria; Hartini H (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
College students’ grade point average (GPA) can be affected by either internal or external factors. Internal factors include intelligences, interests, motivation, and preparedness. Family surroundings and learning environment combined with lecturers’ competencies are categorized as external factors. This study was conducted to study the influence of lecturers’ competencies including pedagogical and professional competencies on students’ GPA at AKJP II Pekanbaru. Analysis was performed with linearity regression test, Shapiro-Wilk normality test, heterocedascity and coefficient of determination test. The Instrument used to gather data was a questionnaire involving 12 lecturers and 30 college students. Data analysis showed significance of the lecturers’ pedagogical and professional competencies on students’ GPA of 67.1% with the value of correlation coefficient is 0.819. It indicated that there was a high correlation between lecturers’ pedagogical and professional competencies and first-year students’ GPA. Key words: Lecturers’ competences, pedagogic, professional, GPA